Feminismo no horário das 9: representações femininas e pautas do movimento feminista em telenovelas brasileiras - Henriques, Mariana Nogueira (2020)
The research investigates how female representations, in Brazilian soap operas, tensioned by hegemony and selective tradition, make the agendas of the feminist movement visible, from the 1960s to 2010. To answer this question, we analyze the soap operas Véu de Noiva (1969), Pecado Capital (1975), Coração Alado (1980), Explode Coração (1995), América (2005) and A Força do Querer (2017). The general objective is to analyze the relations between Brazilian soap operas and the feminist movement, through the representation of female characters, in six soap operas from the 1960s to 2010. Thus, we have as specific objectives: to map the elements of the historical and social context in each moment of the feminist movement in Brazil; verify how the production logics of the soap operas contribute to the representation of the themes through the characters; identify the feminist themes reinforced in the soap operas and recognize the elements used in the construction of the female characters of the soap operas. In order to achieve these objectives, we use the theoretical-methodological assumptions of the cultural studies, approach from which we develop the concepts such as cultural material, mediation, hegemony and tradition, and we also elaborate the cultural-media analysis, based on the cultural theory proposed by Raymond Williams (1979). Besides, we present a history of the feminist movement and its developments, mainly in the Brazilian context, based on Céli Pinto (2003, 2018), Maria Amélia Teles (2003, 2017) and Ilze Zirbel (2007). We also highlight the importance of soap operas in the Brazilian context, characterizing them as cultural products with a potential for articulating representations and also as a catalyst for debates on feminist themes, through Charlotte Brunsdon (1997), Ana Carolina Escosteguy (2003, 2019), Heloisa Buarque de Almeida (2002, 2003) and Clara Meirelles (2009). As a result, the visibility of the agenda in the soap operas is demonstrated through five themes: motherhood, violence against women, empowerment, labor market and sexual diversity, in addition to their consequences. In general, there is a representation through a white, little politicized, individualized and meritocratic feminism, which acts within conservative and traditional limits, reinforcing a double sexual morality. The soap operas and feminism have intense relationships and continuous exchanges, but when represented, it is a “well-behaved” movement, which little reflects the plurality of this struggle, giving voice to stable and conservative models of representations, with a guise of “new discourse”, “current” and “liberal”. Nonetheless, they are extremely important products when dealing with this theme, as they are popular and accessible to everyone, and as they dialogue with easy transit in different contexts. This is intensified in Brazil, due to its great relevance in the various cultural contexts.